Perbandingan Sistem Hukum Antara Indonesia dan Malaysia - Sigit Somadiyono (Wajah Hukum, 2020)
This research is a comparative study of two laws in the world, Indonesian law and Malaysian law. The second study was conducted by comparing the terms of definition, characteristics, objectives, and legal system in the judicial structure. The study aims to look at comparisons of the two to find possible advantages and disadvantages. By comparatively comparative malaysian legal system, in fact, Indonesia is no worse than in Malaysia, in this study it turns out that Indonesia has many advantages that people who work and work in the field of law, and therefore the possibility of the rule of law in Indonesia is still better because many people are law-abiding. The State of Indonesia must create a good legal system, the structure of the court should consider the culture of society such as Malaysia, because law enforcement will be more effective when in accordance with the values or customs that have been formed in the society itself.